Rancang Bangun Sistem Informasi Point of Sale Berbasis Web dengan Metode Scrum - Yusman, Nova Indrayana; Furqon, Muhamad; Wijana, Miki; Rohmanto, Ricky (Jurnal Accounting Information System (AIMS), 2025)
PT. Niasa, like many MSMEs in Indonesia, faced significant operational challenges due to its manual transaction recording and inventory management systems. These manual processes led to crucial issues such as recording errors, data duplication, reporting delays, and difficulty in monitoring stock in real-time. This research aims to design and build a web-based Point of Sale (POS) information system to address these problems. To meet the dynamic needs of MSMEs and ensure the resulting solution aligns with user requirements, the Scrum methodology was chosen for its iterative and adaptive approach. The output of this research is a functional web-based POS system, which includes features for user, product, transaction, and report management. Implementation results show the system successfully improved operational efficiency through increased transaction speed, data accuracy, and faster report generation.